PENGARUH MEDIA PEMBELAJARAN INTERAKTIF TERHADAP MOTIVASI BELAJAR SISWA - Annisa Ramadhani; Darmawati; Risna; Syafitriani; Nurfakina; Emmi Azis; Sahiruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The use of interactive learning materials in teaching and learning is one area where advances in information and communication technology have significantly transformed the educational landscape. The purpose of this article is to examine how interactive learning materials affect students' learning motivation and to explain the ways in which they are used, as well as the factors that promote and hinder their use. This study employed a descriptive qualitative methodology and collected data through a literature review of various sources, including books, scientific publications, and relevant previous research. According to the study's findings, students' learning motivation is positively influenced by interactive learning materials. Students' attention, interest, engagement, and confidence in learning can be enhanced through the use of instructional films, animations, interactive multimedia, educational games, and digital platforms. Furthermore, interactive media make learning less boring and more engaging, encouraging students to participate more actively in the process. However, several barriers to the use of interactive learning materials remain, including inadequate technological resources, instructors' inability to use technology, and varying student abilities in using digital devices. Therefore, to maximize the use of interactive learning media to improve the quality of education and student learning motivation, support from schools, educators, and the government is needed.